2020
DOI: 10.1088/2053-1583/ab7bc5
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers of graphene and 2D material-based gas sensors for environmental monitoring

Abstract: The World Health Organization reported that 4.2 million deaths every year were a direct result of exposure to ambient air pollution (NO 2 , SO 2 , NH 3 , CO 2 , CO, CH 4 ). There is a well-demonstrated global need for high sensitivity, low cost and low energy consumption miniaturised gas sensors to be deployed in a dense network and to be used in an attempt to pinpoint and avoid high pollution hot spots. The high sensitivity of graphene to the local environment has shown to be highly advantageous in sensing ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 385 publications
(441 reference statements)
2
105
0
2
Order By: Relevance
“…2D material gas sensors can be used for environmental monitoring [ 12 ]. These are generally based on the adsorption of analytes such as NH 3 , CO 2 , H 2 O, and NO 2 on the sensor surface [ 1 , 150 , 226 228 ].…”
Section: Gas Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…2D material gas sensors can be used for environmental monitoring [ 12 ]. These are generally based on the adsorption of analytes such as NH 3 , CO 2 , H 2 O, and NO 2 on the sensor surface [ 1 , 150 , 226 228 ].…”
Section: Gas Sensorsmentioning
confidence: 99%
“…An overview of graphene-based nanoelectromechanical resonators was provided in a 2013 review paper [ 9 ], and the utilization of graphene and carbon nanotubes in NEMS was briefly summarized by Zang et al [ 10 ]. However, it has recently become clear that graphene has potential for enabling a much wider range of NEMS sensors, with transition metal dichalcogenide (TMD) and 2D semiconductor materials also emerging in this application space [ 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…After appearing in a previous paper [ 1 ], where it was shown that using graphene as a substrate makes it possible to detect a single gas molecule, a great interest in the performance of graphene-based gas sensors [ 2 , 3 , 4 ] and biosensors [ 4 , 5 , 6 , 7 , 8 , 9 ] arose. To fulfill this program, corresponding adsorption theory is needed (see, for example, [ 10 , 11 , 12 , 13 ] and references on the earlier papers therein).…”
Section: Theoretical Background: Models Of Adsorption On Epitaxialmentioning
confidence: 99%
“…Moreover, the detection of NO2 at these very low concentrations is of interest as a marker for the production of ultra-fine particles [138]. Buckley et al give a comprehensive overview about the sensor performances of graphene based chemiresistors and, depending on the functionalization, LODs ranging from single ppt up to tens of ppm are observed for NO2 [139].…”
Section: Gas Measurementsmentioning
confidence: 99%